3D graphene nanofluids with high photothermal conversion and thermal transportation properties. Issue 3 (17th December 2019) - Bing, Naici; Yang, Jie; Zhang, Yingchun; Yu, Wei; Wang, Lingling; Xie, Huaqing
Abstract : 3D graphene/EG nanofluids show high photothermal conversion and thermal transportation properties and significantly enhance the solar energy utilization. Abstract : Nanofluids as the working fluids enhance solar energy utilization significantly and have led to remarkable progress being made in direct absorption solar collectors (DASCs). In DASCs, nanofluids with better incident light absorption and heat-transfer properties are highly desired. In this study, high surface area and self-standing porous three-dimensional (3D) graphene was easily synthesized through a Ni 2+ -exchange/KOH activation combination method and then dispersing the product in ethylene glycol (EG) as nanofluids. The 3D graphene nanofluids showed greater optical absorption compared to EG in the 250–1400 nm wavelength range. The 3D graphene/EG nanofluids exhibited enhanced thermal conductivity compared with some reported results for graphene nanofluids. When the mass fraction of 3D graphene was 0.064%, the thermal conductivity enhancement was 11.67% at 20 °C. The photothermal conversion efficiency of nanofluids achieved 20% enhancement compared to that of EG. The enhanced photothermal properties of the nanofluids could be attributed to the special architectures of 3D graphene, which can prevent the aggregation of nanosheets and provide more thermal transfer tunnels as well as a longer light scattering distance. This work reveals that 3D graphene has a great application potential in solar thermal systems.